HOW VITAMIN D AFFECTS THE IMMUNE SYSTEM: A REVIEW OF THE LITERATURE - Sandra Khiralla-Gawlik; Konrad Strużek; Agnieszka Kwiatkowska; Ewelina Mączka; Wiktor Tracz; Patrycja Świercz; Kinga Teper; Aleksandra Anna Strzelecka; Aleksandra Ewa Basak (International Journal of Innovative Technologies in Social Science, 2025)
Vitamin D is essential for the proper functioning of the immune system, modulating the immune response through the activation of vitamin D receptors (VDR) in various immune cells. Vitamin D plays a crucial role in protecting against infections, particularly respiratory infections, and its deficiency is associated with an increased risk of autoimmune diseases. Although the results of studies on vitamin D supplementation in the treatment of autoimmune diseases are mixed, there is growing interest in its potential impact on the course of these diseases. This review discusses the mechanisms of vitamin D action in the context of the immune system and its significance in preventing infections and autoimmune diseases. Research indicates the need for further analysis to establish optimal supplementation doses of vitamin D and its effectiveness in different patient groups.